2021
DOI: 10.1177/09544070211004467
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of MR damper based semi-active suspension system using optimally tuned controllers

Abstract: This study assesses the dynamic performance of the semi-active quarter car vehicle under random road conditions through a new approach. The monotube MR damper is modelled using non-parametric method based on the dynamic characteristics obtained from the experiments. This model is used as the variable damper in a semi-active suspension. In order to control the vibration caused under random road excitation, an optimal sliding mode controller (SMC) is utilised. Particle swarm optimisation (PSO) is coupled to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…(i) Dampers: in the study of semiactive suspension systems, the characteristics of the dampers (MR, ER) are of interest to many researchers [5][6][7]. For MR dampers, it uses the physical properties of MR fuids.…”
Section: Related Workmentioning
confidence: 99%
“…(i) Dampers: in the study of semiactive suspension systems, the characteristics of the dampers (MR, ER) are of interest to many researchers [5][6][7]. For MR dampers, it uses the physical properties of MR fuids.…”
Section: Related Workmentioning
confidence: 99%
“…Compared with passive and active suspensions, semi-active suspension systems are characterized by distinguished advantages, including a large adjustment range, fast response, and low energy consumption (Wang et al, 2021). The suspension stiffness can be steered by the damper under external excitations to improve the smoothness and stability of the vehicle (Tharehalli et al, 2021). Magnetorheological dampers (MRDs) utilize smart magnetorheological fluids (MRFs) that exhibit low-viscosity Newtonian fluid properties without an external magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…As a useful device that can provide the resistance force to motion, and consume kinetic energy, magnetorheological (MR) damper is also widely used in vehicle SAS because of its rapid response, low energy consumption and high achievable forces (Floreán-Aquino et al, 2021; Tharehalli et al, 2021; Wang et al, 2021). In Rosli and Moamed (2021), a new cuckoo search algorithm was proposed to enhance the performance of SAS system based on the Bouc-Wen model, the simulation study indicated that the designed controller had faster convergence rate and better fitness value.…”
Section: Introductionmentioning
confidence: 99%